Determinants of foreign direct investment in Lesotho: evidence from cointegration and error correction modeling - Malefa Rose Malefane (South African Journal of Economic and Management Sciences, 2013)
Over the past decade, Lesotho has recorded a substantial increase in levels of foreign direct investment (FDI) inflow, part of it prompted by trade privileges. Building on the extant literature, this study provides an empirical analysis of determinants of FDI in Lesotho. The study looks at how macroeconomic stability, regulatory frameworks, political stability and market size affect FDI.  The evidence from this study shows that some of the foreign enterprises in Lesotho are there to serve a bigger South African market. Also, the country has benefited from a more export-oriented investment promotion strategy. Critical issues however remain that must be addressed if the country is to attract more FDI and retain existing investors .These issues pertain to bureaucratic red-tape, corruption and political instability.